PENERAPAN MEDIA SIMULATOR PHET UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MATERI PENGUKURAN LUAS PADA SISWA KELAS IV SD NEGERI 1 KEDUNGWULUH - Fayza Widya Puspita; Badarudin, Badarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Classroom Action Research is motivated by the low ability of students' mathematical concept understanding on area measurement material in class IV. The purpose of this study is to describe the application of PhET simulator media in learning mathematics on area measurement material for fourth grade students of SD Negeri 1 Kedungwuluh. The subjects of this study were 23 fourth grade students. This study used the Classroom Action Research (PTK) method with the Kemmis and McTaggart model. The results showed an increase in students' mathematical concept understanding ability on area measurement material through the application of PhET simulator media, obtained the percentage of completeness of the mathematical concept understanding ability test cycle I reached 61.9%, and increased in cycle II to 95.45%.